MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN MATEMATIKA KELAS IV SDN 1 SRI MULYA JAYA - Dinda Ardiyani Safitri; Pixyoriza; Binti Khoiriyah (STKIP Subang, 2026)
The low learning outcomes of some fourth-grade students at SDN 1 Sri Mulya Jaya in mathematics were the background for this study. This study aimed to determine the improvement in student learning outcomes after participating in contextual learning in mathematics in the fourth grade at SDN 1 Sri Mulya Jaya. This research is classified as Classroom Action Research (CAR). The subjects of this research were 28 fourth-grade students at SDN 1 Sri Mulya Jaya. The subject studied was mathematics. The data collection techniques used were observation, tests, and documents. The data analysis techniques used were qualitative and quantitative data analysis. The results of this study showed an increase in student learning outcomes with a mastery rate of 68% in Cycle I increasing to 89% in Cycle II. In conclusion, the contextual learning model improved the learning outcomes of fourth-grade students at SDN 1 Sri Mulya Jaya in mathematics, as seen from the 21% increase in learning outcomes